2018
DOI: 10.1017/s0021932018000354
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric variations in different BMI and adiposity levels among children, adolescents and young adults in Kolkata, India

Abstract: The objective of the study was to analyse selected anthropometric features of children, adolescents and young adults from middle-class families in Kolkata, India, by BMI and adiposity categories. Standardized anthropometric measurements of 4194 individuals (1999 male and 2195 female) aged 7–21 were carried out between the years 2005 and 2011. The results were compared by BMI and adiposity categories. Statistical significance was assessed using two-way-ANOVA and linear regression analysis was performed. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Though we agree with Kryst et al (2019) that BMI and adiposity often change concurrently, it is important for the reader to understand that in certain ethnicities a significant proportion of individuals may have a normal BMI but high body fat percentage (normal-weight obesity). The term 'normal-weight obesity' is defined as a body mass index ≤25 kg/m 2 associated with an increased body fat percentage.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Though we agree with Kryst et al (2019) that BMI and adiposity often change concurrently, it is important for the reader to understand that in certain ethnicities a significant proportion of individuals may have a normal BMI but high body fat percentage (normal-weight obesity). The term 'normal-weight obesity' is defined as a body mass index ≤25 kg/m 2 associated with an increased body fat percentage.…”
supporting
confidence: 67%
“…Further to a recently published paper in this journal on the variations in body mass index (BMI) and adiposity levels among young adults and children (Kryst et al, 2019), we would like to highlight that there is yet another pertinent aspect that needs to be considered when using this information in clinical practice. Kryst et al (2019) analysed the selected anthropometric features of children, adolescents and young adults from Indian middle-class families and found that there was a significant positive increment in adiposity (measured by skin fold thickness) with rising BMI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been demonstrated that T cells in MS patients have more IL-6 receptors in peripheral blood than healthy individuals [5]. Due to the fact that it is an inflammatory marker, the amounts increase when the person is overweight or obese, which is determined by means of anthropometric parameters, such as the body mass index (BMI) [6] that is correlated with the individual's adiposity [7]. Clinically speaking, there is a relation to characteristic aspects of the disease, such as relapses and functional disability [4], and with its pathogenesis [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that in the case of children and adolescents, BMI better reflects the changes of the lean body (fat‐free mass) than those concerning adiposity . On the other hand, previous research carried out in the presently examined group showed, that the BMI can be a relatively good predictor of fatness . This may be due to the specifics of the studied population.…”
Section: Introductionmentioning
confidence: 78%